Cowpea haulms as fodder - Tarawali, Shirley A.; Singh, B.; Peters, M.; Blade, S. (1997)
The use of cowpea haulms as fodder is attractive in mixed crop/livestock systems where both grain and fodder can be obtained from the same crop. Traditional farming systems which use the haulms as fodder in Asia, Australia, Africa, and other regions are reviewed. ILRI and I1TA have undertaken joint research to identify accessions with improved grain and fodder yields. Trials were conducted in northern Nigeria to monitor yields in (1) cropping systems trials planted in the rainy season at Kano (Sudan savanna) and (2) dry season evaluation (including fodder quality) at Kano and Kurmin Biri (northern Guinea savanna), where the fodder potential of Cowpea was compared with selected forages. Dry-matter yields from selected cowpea lines at Kano were good, some exceeding 10 t/ha. The role of cowpea as a fodder source is discussed in relation to the major cropping systems in the West African savannas.